البعثات الاستعلامية للبرلمان - عيسو ثابت -مزيلخ المهدي (جامعة المسيلة, 2020)
الحديث عن اللجان البرلمانية الدائمة يعني الحديث عن البرلمان نفسه , فلا يكاد يخلو برلمان في العالم سواء أكان نظامه برلمانيا او رئاسيا من وجود لجان برلمانية تستند إليها مهام ووظائف تسمح للبرلمان بالقيام بعمله , و لعل أغلب هذه البرلمانات تأثرت في تصنيف لجانها بنماذج تنسجم مع طبيعة التكوين هدا البرلمان , تعتمد أغلب البرلمانات العالم على اللجان لأداء وظائفها التشريعية أو الرقابية , ذلك ان أساس عمل البرلمان هو نتاج عمل اللجان , فهي المحرك الرئيسي لعمله , و من هنا يتضح ان الانجاز ملموس للبرلمان هو تطوير عمل لجانه البرلمانية الدائمة و تقوية مهامها و كفاءتها و جديتها في دراسة الموضوعات المحالة أليها لذا أعطى المشرع الجزائري دورا جد فعال لهذه اللجان في ممارسة مهمها الموكلة اليها دستوريا و ذلك ما كان منها سواء في المجال تشريعي او الرقابي على أداء الحكومة. Summary : Talking about permanent parliamentary committees means talking about parliament itself. There is almost no parliaments in the world, whether its system is parliamentary or presidential, of the existence of parliamentary committees on which tasks and functions are based that allow parliament to carry out its work, and perhaps most of these parliaments have been affected by the classification of their committees with models that are consistent with the nature of formation This is the parliament, most parliaments around the world depend on committees to perform their legislative or oversight functions, because the basis of parliament’s work is the result of the committees ’work, as they are the main engine of its work, and from here it becomes clear that the tangible achievement of parliament is to develop the work of its permanent parliamentary committees and to strengthen their tasks and efficiency. Its seriousness in studying the issues referred to it, so the Algerian legislator has given a very effective role to these committees in the exercise of their constitutionally entrusted tasks, and that is what they were in the legislative or oversight sphere on the performance of the government.
Keywords: البعثات الاستعلامية -البرلمان